Tomographic reconstruction of 3D sound speed fields to reveal internal tides on the continental slope of the South China Sea - Dai, Longhao; Xiao, Cong; Zhu, Xiao-Hua; Zhu, Ze-Nan; Zhang, Chuanzheng; Zheng, Hua; Chen, Minmo; Li, Qiang (Frontiers in Marine Science, 2023)
Mirror-type coastal acoustic tomography (MCAT) is an advancement of coastal acoustic tomography (CAT) with a mirror function that enables the nearshore transmission of offshore observation data. Subsurface MCATs are used to monitor small-scale oceanographic phenomena over large areas on the continental slope of the South China Sea (300–1,000 m). This study investigated the performance of MCAT network observation for internal tide monitoring using 3D tomographic inversion. MCAT facilitates communication with each other and is networked. Results of 3D tomographic inversion were highly consistent with the Stanford unstructured nonhydrostatic terrain-following adaptive Navier–Stokes (SUNTANS) model data. The root-mean-square difference of the sound speed obtained by the inversion method was< 1.0 m/s. The high sound speeds induced by the internal tide were well captured by the results of 3D inversion. A high sound speed band of > 1,516 m/s was used as an index of internal tides, which propagated at a speed of 1.9 m/s. Sensitivity experiments demonstrated that a swing of the anchor tether of< 5 m had less impact on sound speed inversion, while distance drifts caused by human activities of > 50 m had a significant influence. The missing of one or several stations owing to natural factors did not generate significant variations in the results of network observation. This study demonstrated that the MCAT network observation strategy, equipped with numerous stations, is more effective in capturing the characteristics of internal tides.